Escribiendo documentos con contenido estadístico (2015)
The Statistics Faculty in the Universidad Santo Tom´as de Colombia has just issued its new semestral publication named Comunicaciones en Estad´ıstica. This is the ﬁrst paper of the journal in which the editorial committee attempts to unify the presentation of the papers that are submitted. It is recalled that this is just a guide that authors could considered but it is clear that variations of the presentation are allowed.